Role of the media in shaping social tensions: а discourse analysis (The Journal of Psychology and Sociology, 2026)
In a multiethnic society he dynamics of national identity, language use, and questions of political and economic sovereignty significantly influence public attitudes and social processes. Nationalism, in this context, functions as a central driver that can escalate societal tensions and contribute to the emergence of conflict potential. Over the past few years, such sentiments have gained momentum amid economic uncertainty, demographic changes, migration trends, and evolving geopolitical conditions. These developments are especially pronounced in the media sphere, where nationalist narratives frequently serve as a catalyst for public polarization and heightened identity-based discourse.  The purpose of the article is to  explore the impact of nationalist discourse in the media on the formation of conflict potential in Kazakhstan. The study incorporates discourse analysis of media publications, including news portals and social media platforms. The data runs from January to October 2024, tracking how nationalism in Kazakhstan has shifted across political, economic, and cultural life. One pattern comes through clearly: nationalist sentiment tends to spike around specific high-profile events. When something happens a summit, an earthquake, a controversial deal it moves quickly through both traditional and digital media. The study identifies key trends in the dissemination of nationalist discourse and contributes to a deeper understanding of the media’s role in shaping social tension. The findings offer valuable insights for further research into societal conflict potential and for the development of strategies aimed at managing information processes.Keywords: conflict potential, nationalism, rhetoric in the media, the role of the media, discourse analysis.